Hero stone depicting a human figure mounted on horseback - Temples of India Project Team (Jio Institute, 2024)
Seen here is a smaller hero stone, characterized by its simple ornamentation and minimal figural depiction. It features only a human figure mounted on horseback, representing the deceased hero. The plain stone surface of the hero stones may have originally included epigraphical etchings.